Job satisfaction and turnover intention among the nurses at Puteri Specialist Hospital, Johor Bahru / Mohd Nizam Hj Ali, Mohd Nor A. Aziz & Halela Shah - Hj Ali, Mohd Nizam; A. Aziz, Mohd Nor; Shah, Halela (2010)
This study examines the relationship between five factors of job satisfaction which is working environment, quality of supervision, relationship with co-workers, promotion opportunities, monetary compensation, and turnover intention among the nurses at Puteri Specialist Hospital, Johor Bahru (PSHJB). The study also hypothesized there is a turnover intention dimension that has the highest mean, a unit that shows the highest turnover intention and there is a difference in the demographic factors of level of education and length of services to the turnover intention. Questionnaire was used as a research instruments to obtain data for analysis. A total of 190 out of 211 nurses (90%) were randomly selected as the sample of study. From the 190 questionnaire forms distributed, 169 or 89% were returned and data was analyzed by "Statistical Package for Social Science" (SPSS Window) Version 17.0. The findings of the study show that 42% of the respondents are between the ages of 22 to 25 years old and 36.1 percent of the respondents have been working with PSHJB, for between one to three years. The result of the job satisfaction and turnover intention shows a very low relationship. Monetary Compensation demonstrates the most significant relationship with turnover intention with operating theatre's nurses shows the highest turnover intention. Demographic factors (Age, level of education and length of services) did not show any significant difference with turnover intention. Based on the findings, recommendation and suggestions for improvement and further research are presented.